Effect of soluble probiotic on production performance of Akar Putra chicken - Jawad, Hasan S. A.; Idris, Lokman Hakim; Naji, Saad A.; Abu Bakar @ Zakaria, Md Zuki; Kasim, Azhar (Asian Network for Scientific Information, 2016)
The present study was conducted to investigate the effect of soluble probiotic on the production parameters of local Malaysian chicken (Akar Putra). A total of seventy two 1-day-old Akar Putra chicks were randomly assigned to three treatment groups, each having 3 replicates of 8 chicks. The treatments were as follows: (T1) control, (T2) probiotic supplemented at 1 g/liter tap water, (T3) probiotic supplemented at 2 g/liter tap water. The results revealed that supplementation of soluble probiotic at both the rates resulted in an improved performance of male and female Akar putra chicken. Birds who received 2 g of prepared probiotic per liter of water (T3) exhibited highly improved (p<0.05) body weight, weight gain and feed conversion ratio than other groups. It can be concluded that supplementation of prepared soluble probiotic would be economically beneficial in improving the production performance and health status of Akar Putra chicken.